The knowledgeable patient: investigating the role of lay knowledge in the production of health - Karlsson, M (2007)
In this paper, we analyse the role of knowledge in an individual's production of health. We investigate the importance of various factors which potentially influence an individual's decision to seek health related knowledge, and then estimate what impact such knowledge has on individual health. Using a cross-sectional dataset of middle-aged and old UK residents, we estimate a bivariate probit model which accounts for the possible endogeneity of knowledge in the health production function. We find that knowledge has a strong effect on self-assessed health, and that this variable tends to dominate other typical covariates with health, such as education and gender. Furthermore, we find tha the parameter estimates for individuals with chronic conditions are systematically different from those of others, but no results are qualitatively different in these two subgroups.